PERLINDUNGAN HUKUM TERHADAP KONSUMEN TERKAIT DENGAN KENAIKAN HARGA MASKER DI MASA PANDEMI COVID-19 - Nurhotia Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
The world is currently facing Covid-19, where the virus has spread throughout the world, including Indonesia. The President and Government appealed to the public to maintain health, follow health protocols such as wearing masks when outside the home. Lots of people buy basic necessities, so there is panic buying. Masks are currently experiencing scarcity, considering that masks are one of the basic necessities, so they are expensive. The increase in the price of these masks has made it difficult for less fortunate consumers to buy masks. Then what about the legal protection for consumers regarding the expensive price of masks? The author examines these problems using normative legal research methods. Research data shows people who complain about these expensive masks. The government should give the community masks periodically or free every once a month, so that people who are less fortunate can also have masks to prevent the corona virus.